LEGAL REGULATION ARCHIVE AND LIBRARY CASE IN UKRAINE - Довжук, Ігор (SWorldJournal, 2024)
The most important normative legal acts regulating the activities of archival and library institutions of Ukraine are considered. Such legal acts contribute to the creation of conditions for the creative development of the individual, raising the cultura